The Ablation of Envelope Protein Glycosylation Enhances the Neurovirulence of ZIKV and Cell Apoptosis in Newborn Mice - Yanqing Guo; Linlin Bao; Yanfeng Xu; Fengdi Li; Qi Lv; Feiyue Fan; Chuan Qin (Journal of Immunology Research)
Zika virus (ZIKV) has attracted the wide global attention due to its causal link to microcephaly. In this study, two amino acid (aa) mutation (E143K and R3394K) were identified at the fourth generation (named ZKC2P4) during the serial passage of ZIKV-Asian lineage ZKC2/2016 strain in the newborn mouse brain, while another seven aa deletions in envelope (E) protein were detected in ZKC2P6. ZKC2P6 is a novel nonglycosylated E protein Asian ZIKV we first identified and provides the first direct supporting evidence that glycosylation motif could be lost during the passage in neonatal mice. To study the impact of E protein glycosylation ablation, we compared the pathogenicity of ZKC2P6 with that of ZKC2P4. The results showed that the loss of E protein glycosylation accelerated the disease progression, as evidenced by an earlier weight loss and death, a thinner cerebral cortex, and more serious tissue lesions and inflammation/necrosis. Furthermore, ZKC2P6 exhibited a greater ability to replicate and caused severer cell apoptosis than that of ZKC2P4. Therefore, the ablation of E glycosylation generally enhances the neurovirulence of ZIKV and cell apoptosis in newborn mice.